Implementasi Fuzzy Logic dan Ellie: Buddy AI Pada Companion Dalam Game Survival Horror - Winsen Wonady; Kristo Radion Purba; Rudy Adipranata (Jurnal Infra, 2017)
The development of the game is now very rapidly growing. As the game develops, making AI (Artificial Inteligence) in the game even more advanced. There are many types of AI that are usually used in the game including AI NPC Companion is AI that will accompany players during the game. Game will be developed using Unity Application and using C # language programming language. In the game players will be accompanied by NPCs who use Fuzzy Logic combined with Ellie: Buddy AI as AI controller. In the game players will also face zombies and bandits as enemies that will use rulebase as AI nya. The end result of this game is a survival horror game genre with NPC Companion feature. The testing done at the end of the segment is testing of the application, testing of NPC, testing of Enemies, testing of players and Comparison between NPC Companion and AI bandit.The final result of testing is that the game can run smoothly, AI NPC and Enemy can run with Well, and Control player can be used well, At the end result of comparison NPC found can do action more varied compared to AI bandit.